Does Belt and Road Initiative Hurt Node Countries? A Study from Export Perspective. Issue 7 (28th May 2019) - Mao, Haiou; Liu, Guanchun; Zhang, Chengsi; Muhammad Atif, Rao
ABSTRACT: The existing studies on the Belt and Road Initiative (BRI) primarily explain its impact on China's trade or foreign direct investment, whereas its impact on node countries' export performance to China has not been examined. By considering the BRI as external policy shock and incorporating "Five Connection" indicators in the model, this article describes the mechanism and impact of the BRI on node countries' exports to China. By using propensity score matching and a difference-in-difference approach, we tackle the endogeneity problem caused by self-selecting into the BRI node-country group. The estimates indicate that the BRI has an overall positive effect on node countries' exports to China with an upward trend. The study also observes that facility connection, trade barriers reduction, financial integration, and people-to-people bond are efficient ways to enhance node countries' exports. Further, the regional heterogeneity analysis finds a smaller positive effect on North African and on central and East Asian economies, while higher on other regions.